2008
DOI: 10.1128/cvi.00435-07
|View full text |Cite
|
Sign up to set email alerts
|

Role of Protein Tyrosine Kinase and Erk1/2 Activities in the Toll-Like Receptor 2-Induced Cellular Activation of Murine B Cells by Neisserial Porin

Abstract: Neisserial porins are potent immune adjuvants and have been demonstrated to stimulate and induce the activation of human and murine B lymphocytes. Their immunopotentiating ability is due largely to the upregulation of the surface expression of the costimulatory ligand CD86 (B7-2) on B cells and other antigenpresenting cells. Porin-induced activation is dependent on the innate immune pattern recognition receptor Toll-like receptor 2 (TLR2). These data have led us to investigate the signal transduction events in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 65 publications
2
19
0
Order By: Relevance
“…Most intracellular antiapoptotic factors are under transcriptional control of NF-B, which therefore plays a major role in prevention of cell death (30). NF-B activation is induced by whole neisseriae and neisserial porins in various cell systems (5,13,21,23,27,35,59,77); in particular, PorB induces NF-B activation in a manner dependent on TLR2 (46,48,52), a receptor that is not present in HeLa cells (78). To determine whether PorB could induce TLR2-independent NF-B activation in these cells, multiple approaches were used.…”
Section: Mitochondrial Localization Of Porb Is a Time-sensitive Tlr2mentioning
confidence: 99%
See 1 more Smart Citation
“…Most intracellular antiapoptotic factors are under transcriptional control of NF-B, which therefore plays a major role in prevention of cell death (30). NF-B activation is induced by whole neisseriae and neisserial porins in various cell systems (5,13,21,23,27,35,59,77); in particular, PorB induces NF-B activation in a manner dependent on TLR2 (46,48,52), a receptor that is not present in HeLa cells (78). To determine whether PorB could induce TLR2-independent NF-B activation in these cells, multiple approaches were used.…”
Section: Mitochondrial Localization Of Porb Is a Time-sensitive Tlr2mentioning
confidence: 99%
“…A correlation between the antiapoptotic effect of PorB and activation of NF-B has not been shown so far, although our group has demonstrated that PorB activates NF-B in a Tolllike receptor 2 (TLR2)-dependent manner (43,46,48,52). Interestingly, various human and murine cell types are protected from apoptosis by PorB (23.…”
mentioning
confidence: 99%
“…Studies on Neisseria spp. porins are implicated in TLR mediated NFκB activation which occurs via Raf-1-MEK1/2-MAPK pathway; (Massari et al 2003 ;MacLeod et al 2008 ). H. infl uenzae porin P2 and porins of Salmonella and Neisseria also activate the MAPK pathway (Galdiero et al 2002(Galdiero et al , 2003cVitiello et al 2004 ;MacLeod et al 2008 ).…”
Section: Signaling Cascades Initiated By Porinsmentioning
confidence: 97%
“…porins are implicated in TLR mediated NFκB activation which occurs via Raf-1-MEK1/2-MAPK pathway; (Massari et al 2003 ;MacLeod et al 2008 ). H. infl uenzae porin P2 and porins of Salmonella and Neisseria also activate the MAPK pathway (Galdiero et al 2002(Galdiero et al , 2003cVitiello et al 2004 ;MacLeod et al 2008 ). The three-dimensional structure model of porin P2 constructed on the basis of crystal structure of K. pneumoniae OmpK36 and Escherichia coli PhoE and OmpF predict that the domains of surface exposed loops are involved in activation of signal transduction pathway (Table 6.1 ) .…”
Section: Signaling Cascades Initiated By Porinsmentioning
confidence: 97%
“…Since PorB from NM and NL induce TLR2 cell activation via similar, but not identical signaling mechanisms, we examined individual pathways downstream of TLR2 using specific inhibitors of MAPKs (p38, ERK1/2 and JNK) and NF-κB pathways [24, 38]. While inhibition of NF-κB strongly reduced intracellular organisms, variability was observed for MAPKs: inhibition of JNK signaling generally led to lower intracellular bacteria, the effect of ERK1/2 inhibition was less considerable and that of p38 inhibition was rather dubious, consistent with previous observations [26] and with a potential function redundancy among these pathways.…”
Section: Discussionmentioning
confidence: 99%